2000
DOI: 10.1093/ejo/22.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Functional and social discomfort during orthodontic treatment - effects on compliance and prediction of patients' adaptation by personality variables

Abstract: During the course of treatment orthodontic patients frequently endure a number of functional complaints and are anxious about their appearance. The aims of this longitudinal study were to follow the progress of patients' adaptation to discomfort, to elucidate the putative relationship between the type of appliance worn and functional and social discomfort experienced, to study potential predictability by their attitude to treatment and to evaluate the effects of discomfort as predictors of patients' compliance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
96
3
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 17 publications
14
96
3
8
Order By: Relevance
“…Eating, speaking, and smiling were the daily perfor- mances most commonly affected (Table 1), supporting previous findings by Scheurer et al, 5 Sergl et al, 2 and Mandall et al 9 Scheurer et al 5 found that biting and chewing were the most painful everyday activities affected in the week after insertion of appliances. Sergl et al 2 reported that the main short-and long-term impacts of wearing appliances were on speech and swallowing as well as in reduced confidence when in public. And Mandall et al 9 reported that undergoing orthodontic treatment caused impacts related to aesthetic as well as to functional limitations.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Eating, speaking, and smiling were the daily perfor- mances most commonly affected (Table 1), supporting previous findings by Scheurer et al, 5 Sergl et al, 2 and Mandall et al 9 Scheurer et al 5 found that biting and chewing were the most painful everyday activities affected in the week after insertion of appliances. Sergl et al 2 reported that the main short-and long-term impacts of wearing appliances were on speech and swallowing as well as in reduced confidence when in public. And Mandall et al 9 reported that undergoing orthodontic treatment caused impacts related to aesthetic as well as to functional limitations.…”
Section: Discussionsupporting
confidence: 83%
“…Over the short-and long-term courses of treatment, fixed or functional appliances have been previously reported to produce a higher intensity of discomfort than removable appliances. 2,[5][6][7] The present findings provide useful information in relation to the likelihood of pain, discomfort, and side effects for patients undergoing orthodontic treatment. However, further studies are needed, especially longitudinal studies, to assess the change over time of the condition-specific impacts related to wearing orthodontic appliances.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…A study has found that complaints of fixed appliances included altered speech and swallowing 4 and it would be wise to warn patients regarding this. Fixed orthodontic appliances are not known to inhibit the function of the soft tissues during the oral phase of swallowing or the gag reflex.…”
Section: Parental Competencementioning
confidence: 99%